Student as a player – projecting didactic tools in early art education and academic education - KARCZMARZYK, Małgorzata; BANASIAK, Małgorzata (Journal of Education, Technology and Computer Science, 2014)
The modern student is privately a player. He/she spends hours sitting at thecomputer and experiencing many positive feelings such as joy, surprise, curiosity,excitement. Is there anything more exciting than the adventure in a virtualworld and at the game?In our presentation we will try to provide an educational game as an interestingopportunity to teach and study early school children and the students – futureteachers. Projecting educational games (both board and computer ones) and testingthem, can be a wonderful way to develop students’ interests and to learn andstudy in an interesting way. We will present our projects conducted with the students of the Universityof Gdansk, of Gdansk Higher School “Athenaeum”, and of the Nicolaus CopernicusUniversity in Torun, which may provide inspiration for educational andteaching activities of other teachers and show that science can also be interestingand adventurous.